Genetics of stem rust resistance in four bread wheat cvs. HD2733, HD2768, HD2781 and HD2784 - R.C. MATHURIA*, P. BAHADUR and (Indian Phytopathology, 2008)
The nature of inheritance of resistance to stem rust (Puccinia graminis f. sp. tritici) of wheat in four bread wheat cultivars was studied at Indian Agricultural Research Institute, New Delhi, during rabi 2002-03 to 2005-06. The genetic analysis confirmed three dominant genes for resistance to stem rust in HD2768, two dominant independent genes each for resistance in HD2733 and HD2784, and one dominant gene in HD2781. Analysis of BC1 and BC2 with pathotype 122 (7G11) confirmed the above number of genes. F2 segregation of intercrosses HD2733 x HD2781 and HD2781 x HD2784 showed different genes for resistance in above cultivars. An adult plant resistant gene (Sr2) was also identified in HD2733, HD2781 and HD2784 based on mottling effect on the seedlings.